Pelatihan Pengelolaan Sampah Organik menggunakan Maggot BSF di Desa Tambaksari - Semerdanta, Wardah; Agus Salim, Muhammad Yusuf; Nur Aini, Adelia Fitri; Falasifa, Mohamad Amiq; Ariyandito, Ferry; Wijayaf, Arif (CV.ITTC INDONESIA, 2025)
Tambaksari village still faces the problem of organic waste management, mainly due to the lack of an efficient treatment system and the lack of public awareness of the importance of waste management. If the village is to become a tourist spot, environmental sustainability must be considered. To address this issue, local people were provided with training on how to decompose organic waste using Black Soldier Fly (BSF) larvae. This program employed a participatory action research (PAR) approach, which actively involved the community in the process, from surveys and group discussions to implementation, which included the creation and utilization of household-scale biopond. To assess the effectiveness of the material presentation, an evaluation was conducted through a pre-test and post-test. The results showed a significant increase in participants' understanding, with an average score increase of 21.25%. This program not only provides solutions to waste problems but also encourages the creation of a new culture of sustainable environmental management at the local level.